(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Introduction: Healthful school environments are essential for student well-being and academic performance. In Southwest Nigeria, gaps in infrastructure, sanitation, and policy implementation compromise the quality of public secondary schools. Objective: This study assessed the healthful school environment of public secondary schools in Ado-Ekiti, focusing on school site, infrastructure, classroom standards, and staff awareness of environmental health practices. Method of Analysis: A descriptive cross-sectional survey was conducted among 300 teachers and administrative staff across 21 public secondary schools. Data were collected using structured questionnaires and analyzed using SPSS 25. Descriptive statistics and chi-square tests were employed. Results: Most schools (85.7%) were located near major roads, while only 17.7% were near rivers or streams, and 8% near waste disposal sites. Water facilities were available in 86.7% of schools, and emergency health services in 69.1%. Only 31.2% of schools had adequate gender-sensitive toilets, and 41.5% had safe recreational facilities. Classroom assessments showed 73.3% were well-ventilated, but only 13.3% had adequate lighting, and 33% had sufficient furniture. Less than half of staff (47.3%) had received training on environmental health, and only 39.7% participated in sanitation monitoring. Conclusion: Public secondary schools in Ado-Ekiti demonstrate partial compliance with healthful environment standards. Critical gaps in sanitation, classroom quality, recreational facilities, and staff training highlight the need for targeted infrastructure improvements, WASH interventions, and policy enforcement to promote safe and conducive learning environments.